Strengthening Teacher Professionalism in the Digital Era: A Meta-Analysis of Digital Competence and Creativity as Drivers of Contextual Performance - Mulyaningrum, Vicihayu Dyah; Widodo, Widodo; Lapasau, Merry; Dewi, Ery Lukito (Jurnal Pendidikan Progresif, 2025)
Strengthening Teacher Professionalism in the Digital Era: A Meta-Analysis of Digital Competence and Creativity as Drivers of Contextual Performance. Objectives: This study aims to synthesize empirical findings on the relationships among digital competence, creativity, and teachers' contextual performance through a systematic literature review and meta-analysis. Methods: A total of 26 empirical articles published between 2020 and 2025 were selected using the PRISMA protocol and established inclusion criteria. Among these, fourteen studies investigated the relationship between digital competence and contextual performance, whereas twelve studies examined the relationship between teacher creativity and contextual performance. Effect sizes were extracted as correlation coefficients (r), and all analyses were conducted using JASP. Findings: The meta-analysis results indicated that digital competence had a positive and significant effect on teachers' contextual performance (ES = 0.061; Z = 3.625; p < .001). The effect size was small, which can be explained by the fact that digital competence is only one factor among various determinants of contextual behavior, such as intrinsic motivation, creativity, and organizational commitment. However, this small effect remained consistent across studies, indicated by non-significant heterogeneity (Q = 0.875; p = 1.000). This finding indicates that digital competence continues to contribute to teachers' adaptability, collaboration, and proactive behavior in digital work contexts. The validity of this estimate was strengthened by Egger's test (p = 0.350), which indicated the absence of publication bias. Analysis of teacher creativity also showed a positive and significant effect on contextual performance (ES = 0.067; Z = 3.305; p < .001). Despite being a small effect, creativity consistently contributed to variations in teachers' contextual behavior, particularly in initiative, teamwork, and engagement in non-instructional activities. The homogeneity across studies supports the stability of this relationship. Conclusions: Overall, these findings confirm that digital competence and creativity play essentials supporting roles in shaping teachers' contextual performance in the digital education era. Both reinforce adaptive, collaborative, and contribution-oriented professional behavior, thus providing an empirical basis for strategies to improve teacher professionalism that are more relevant to the demands of the modern education ecosystem. Keywords: digital competence; teacher creativity; contextual performance; meta-analysis.